Localized pemphigus vegetans without mucosal involvement - V K Jain; N Jindal; S Imchen (Wolters Kluwer Medknow Publications, 2014)
Pemphigus vegetans is a rare variant of pemphigus vulgaris. A 62-year-old woman presented with erythematous moist vegetative plaque on the left breast and left groin. There was no mucosal involvement. Histopathological and direct immunofluorescence findings were suggestive of pemphigus vegetans. She showed excellent response to oral steroids. Literature is scarcely available on the limited involvement with pemphigus vegetans without mucosal involvement.